New technical approaches for 3D morphological imaging and quantification of measurements - Brenna, Cinzia; Khan, Arif ul Maula; Picascia, Tiziana; Sun, Quanchao; Heuveline, Vincent; Gretz, Norbert (The anatomical record, 2020)
3D imaging is becoming more and more popular, as it allows us to identify interactions between structures in organs. Furthermore, it gives the possibility to quantify and size these structures. To allow 3D imaging, the tissue sample has to be transparent. This is usually achieved by using optical tissue clearing protocols. Although using optical tissue clearing often results in perfect 3D images, these protocols have some pitfalls, like long duration of sample preparation (up to several weeks), use of toxic substances, damage to antibody staining, fluorescent proteins or dyes, high refractive indices, and high costs of sample processing.Recently we described [Huang et al., Scientific Reports 9(1): 521 (2019)] a fast, safe, and inexpensive ethyl cinnamate (ECi) based optical tissue clearing protocol. Here, we present extensions of our protocol with respect to the deparaffinization of old paraffin-embedded samples allowing 3D imaging of the blocks. In addition, we learned to remove ECi from the samples allowing the use of routine immunolabeling protocols. Furthermore, we demonstrate new pictures of lungs after expansion microscopy and adaptation of already existing protocols. The aim of our work is, in summary, to describe the advances in these methodologies, focusing on the morphological imaging of kidneys and lungs.
First published: 12 June 2020
Gesehen am 05.11.2021